P053 Heterotopic ossification after COVID-19 infection - case report. (23rd April 2022) - Chang, Yvonne; Stathopoulou, Eleni
Abstract: Background/Aims: Heterotopic ossification (HO) is the abnormal formation and deposition of mature lamellar bone within soft tissue, associated with trauma, surgery, neurologic injury and prolonged immobilisation. Several recent case reports have demonstrated this condition in COVID-19 patients requiring mechanical ventilation. Methods: We present a case of heterotopic ossification in the shoulder after a long stay in intensive care unit (ICU) due to COVID-19 infection. Results: A 55-year-old man with stable psoriatic arthritis on sulfasalazine was admitted to ICU for mechanical ventilation after contracting COVID-19 infection. After discharge from ICU, he began noticing increasing right shoulder pain with restricted movements of abduction, internal and external rotation. His serum alkaline phosphatase was moderately elevated. Despite physiotherapy and NSAIDs, there was slow improvement. Shoulder x-ray showed significant bony overgrowth around proximal humerus which was initially thought to be part of his psoriatic arthritis. It was confirmed at Rheumatology/Radiology MDT to be heterotopic ossification. A computed tomography of the right shoulder was requested to evaluate the extent of the condition and orthopaedic advice was sought. Conclusion: There are many factors contributing to the development of heterotopic ossification including trauma, spinal cord injury, brain injury, hypoxia, prolonged immobilisation with limitation of joint movement and prolonged bed rest which cause alterations in calcium homeostasis, male sex and over 60 years of age. New onset joint pain and stiffness in patients who have recovered from COVID-19 especially those who had long ICU stay should be further investigated for this condition. Treatment includes analgesia and physiotherapy with potential surgical intervention. Disclosure: Y. Chang: None. E. Stathopoulou: None.